Features of Supplemental Feeding Implementation and Physical Development of Infants - Yulia O. Tkach; Larisa V. Levchuk (Union of pediatricians of Russia, 2023)
Background. Balanced feeding with timely supplemental feeding implementation ensures optimal rates of physical and psychomotor development. It is the most effective way for preventing chronic non-communicable diseases and programming health during human life.Objective. The aim of the study is to analyze the timing of the supplemental feeding administration in infants regarding their physical development.Methods. Online questionnaire was developed via Google Forms. Responses from mothers of 108 children aged from 5 months to 3 years were analyzed. Physical development was evaluated via the WHO Anthro program.Results. The timing of first supplemental feeding implementation corresponded to the Optimizing program on infants feeding in Russian Federation (2019) in 89.8% (n = 97) of cases, after 6 months - 6.5% (n = 7) of cases, and before 4 months - 3.7% (n = 4) of cases. The first supplemental feeding most commonly was vegetable puree (65.7%; n = 71), less often - porridge (18.5%; n = 20), or fruit puree (13.9%; n = 15). The meat puree was implemented after 8 months in 57.4% (n = 62) of cases. The mean of z-score for the body mass index to age ratio in children with late supplemental feeding implementation was − 1.1 ± 0.58. It has turned out to be significantly lower than in case of timely administration: 0.08 ± 0.11; p ≤ 0.05.Conclusion. Late supplemental feeding administration (especially foods with high biological value) resulted in nutritional status violation through body weight deficiency in children both on breastfeeding and formula feeding.